Comparison of management options for spontaneous bleeding into soft tissues in patients with COVID-19 - A. E. Tyagunov; D. Y. Trudkov; A. Y. Polyaev; E. A. Stradymov; M. V. Baglaenko; S. V. Mosin; A. V. Sazhin (Scientific Reports)
Abstract Spontaneous bleeding into soft tissues was a common complication of anticoagulant therapy among critically ill patients during the COVID-19 pandemic. This study sought to evaluate the impact of different treatment methods on survival among COVID-19 patients with active or self-resolved spontaneous bleeding into soft tissues. Methods used to treat CT-confirmed spontaneous hematomas in COVID-19 patients included nonoperative management (NOM), angiography (AG) with transarterial embolization (TAE) and open surgery (OS). A total of 227 participants with spontaneous hematomas into soft tissues were enrolled in this retrospective single-center study at a COVID-19-hospital between March 3, 2020 and March 3, 2022. NOM was used in 144 patients, including 51 patients with extravasation on CT; 60 patients with extravasation on CT were subjected to AG, which was followed by TAE in 41 patients. Open surgery was performed on 23 patients. The choice of treatment strategy did not have any effect on 30-day mortality among patients with extravasation. Mortality did not differ between the OS, NOM and AG/AG+TAE groups (p = 0.094). In the multivariate logistic regression model, OS and NOM did not increase the risk of death, in comparison with AG, respectively (OR 1.53 [95% CI: 0.35-7.37]; p = 0.579 and OR 1.39 [95% CI: 0.53–3.72]; p = 0.501).